School choice and loss aversion - Vincent Meisner; Jonas von Wangenheim (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
Extensive evidence suggests that participants in the direct student-proposing deferred-acceptance mechanism (DSPDA) play dominated strategies. In particular, students with low priority tend to misrepresent their preferences for popular schools. To explain the observed data, we introduce expectationbased loss aversion into a school-choice setting and characterize choiceacclimating personal equilibria in DSPDA. Truthful equilibria can fail to exist, and DSPDA might implement unstable and more inefficient allocations in both small and large markets. Specifically, it discriminates agains students who are more loss averse or less overconfident than their peers, and amplifies already existing (or perceived) discrimination. To level the playing field, we propose serial dictatorship mechanisms as a strategyproof and stable alternative that is robust to these biases.
Keywords: C78; D78; D82; D81; D91; 330; Market design; Matching; School choice; Reference-dependent preferences; Loss aversion; Deferred acceptance